Equatorial Guinea : Public Investment Management Review - Munoz Moreno, Rafael (World Bank, Washington, DC, 2014)
The chapter offers concise diagnostics of the public investment management (PIM) system in Equatorial Guinea. It provides specific examples of how underperforming institutions throughout the investment process raise the risk of selecting white elephants, reducing the value for money of investment projects and undermining the quality of completed projects. Politically compatible recommendations unlock the opportunities for overcoming the major institutional and procedural binding constraints to improve the country s PIM in a sequenced manner. The set of analysis and derived policy implications provides policy insights for countries in similar situations that need clear and pragmatic guidance on where to start building a better performing investment system in a challenging country context. Equatorial Guinea, one of the poorest countries in Africa prior to the discovery of hydrocarbons in the 1990s, has made a significant effort to transform this new wealth into public infrastructure. After a first phase focus on improving the dilapidated infrastructure and supply of capital in the country, the Government embarked on a second investment round to implement the National Development Plan, adopted in 2007 with the aim of diversifying the economy out of petroleum production and improving living standards. However, the country is ill equipped for such a massive investment effort, with oil comprising 22 percent of GDP in 2008. Public expenditure is thwarted by cumbersome administrative procedures encouraging informal shortcuts that render the rigorous capital budgeting both irrelevant and impossible. The absence of reliable budget data undermines the monitoring of budget implementation. As a result, the public budget fails as a tool for resource allocation and control. The country s business laws promote a liberalized economy but the overall business climate remains poor. Efforts to create an atmosphere conducive to investor interest have not been sufficient and application of the laws remains selective, corruption among officials is widespread, and business rules and institutions are nontransparent. The Government is attempting to create a more favorable investment climate to promote foreign investment, for example, by adding numerous incentives to its investment code for job creation, such as training, promotion of nontraditional exports, support of development projects and indigenous capital participation, freedom for repatriation of profits, exemption from certain taxes and capital, and other benefits.